Towards environmental management of WEEE in Brazil: evaluating the impacts of recycling plastics - Abner Fernandes Souza da Silva; Guilherme Andreazza de Freitas; Diogo Aparecido Lopes Silva; Jane Maria Faulstich de Paiva; Juliana Mendes Campolina; Virgínia Aparecida da Silva Moris (Environmental Science and Pollution Research, 2026)
Plastic fractions recovered from waste electrical and electronic equipment (WEEE) are growing rapidly worldwide, yet their net environmental benefit remains under-quantified—especially in emerging economies such as Brazil, where recycling infrastructure is still maturing. Acrylonitrile–Butadiene–Styrene (ABS) and High-Impact Polystyrene (HIPS) together account for a large share of this stream and offer high material value if efficiently reprocessed. This study applies ISO 14040/14044 life cycle assessment to quantify the impacts of recycling ABS and HIPS collected from Brazilian WEEE. Foreground data from an industrial plant in Sorocaba were modeled with ReCiPe 2016 midpoint indicators. Extrusion emerged as the dominant hotspot, contributing 75.2% (ABS) and 85.7% (HIPS) of total impacts, whereas transport accounted for < 5%. Cutting extrusion energy by 30% reduced global warming potential (GWP) by 25% for HIPS and 22% for ABS, while switching to Brazil’s renewable-rich grid reduced impacts across the main categories. Compared with virgin resin, recycling resulted in substantially lower global warming impacts for both HIPS and ABS. The sensitivity analysis showed that adopting an economic allocation approach led to lower environmental impacts compared with mass-based allocation for both ABS and HIPS. Optimizing extrusion energy and adopting low-carbon electricity are therefore critical to maximizing the environmental benefits of WEEE-plastic recycling. Beyond technical insights, these results provide evidence to guide public policies that promote recycling infrastructure and energy efficiency, while reinforcing that recycled plastics offer substantially lower environmental burdens compared with virgin resources.